Metabolite Profiling of the Indian Food Spice Lichen, Pseudevernia furfuracea Combined With Optimised Extraction Methodology to Obtain Bioactive Phenolic Compounds - Kalra, Rishu; Conlan, Xavier A.; Areche, Carlos; Dilawari, Rahul; Goel, Mayurika (Frontiers in Pharmacology, 2021)
Pseudevernia furfuracea(L.) Zopf (Parmeliaceae) is a well-known epiphytic lichen commonly used in Indian spice mixtures and food preparations such as curries. This study is an attempt to find the best extraction methodology with respect to extractive yield, total polyphenolic content (TPC), total flavonoid content (TFC) and antioxidant activities of lichen P. furfuracea. Two phenolic compounds, atraric acid and olivetoric acid were isolated and quantified in their respective extracts with the aid of reverse phase high performance liquid chromatography (RP-HPLC). The highest concentration of both the compounds, atraric acid (4.89 mg/g DW) and olivetoric acid (11.46 mg/g DW) were found in 70% methanol extract. A direct correlation was also observed between the concentrations of these compounds with the antioxidant potential of the extracts which highlights the contribution of these compounds towards the antioxidant potential. Moreover, scanning electron microscopy and HPLC analysis which was used to study the effect of pre-processing on extraction process highlighted the capacity of a mixer grinder technique for improved separation of surface localized metabolites and enrichment of the fraction. An investigation of the chemical profile of the bioactive extract 70% methanol extract using UHPLC-DAD-MS lead to tentative identification of forty nine compounds. This extract was also assessed towards HEK 293 T cell line for cytotoxicity analysis. Concentration range of 0.156 µg/mL to 100 µg/mL of PF70M extract exhibited no significant cell death as compared to control. Further, the active extract showed protective effect against hydroxyl radical’s destructive effects on DNA when assessed using DNA nicking assay.